Análisis de la ley orgánica para la promoción del trabajo juvenil, regulación excepcional de la jornada de trabajo, cesantía y seguro de desempleo y su reglamento de aplicación - Carreño Rodríguez, José Danilo (2018)
The analysis that is made to a law must always be for the purpose of discovering or finding the pro and cons of the same, in this particular case we will identify if the application is appropriate to the interests or benefits of workers' rights . Through a whole process of investigation it will be possible to determine in detail what it means, concerns or concerns the Organic Law for the Promotion of Youth Labor, Exceptional Regulation of the Working Day, Unemployment and Unemployment Insurance and its Regulation of Application………